N `-[(E)-2,6-Dichlorobenzylidene]pyrazine-2-carbohydrazide - Howie, R.A.; de Souza, M.V.N.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title compound, C(12)H(8)Cl(2)N(4)O, is non-planar, the dihedral angle formed between the pendant pyrazine and benzene rings being 12.55 (11)degrees. An intramolecular N-H center dot center dot center dot N hydrogen bond occurs. The amide groups self-associate via N-H center dot center dot center dot O hydrogen bonding, forming supramolecular chains with base vector [101], which are stabilized by C-H center dot center dot center dot O contacts. C-H center dot center dot center dot N interactions are formed orthogonal to the chains.